In vitro and in vivo antibacterial activity of tazobactam/piperacillin - Minami, Shinzaburo; Yamada, Hisashi; Okamoto, Seiki; Narita, Hirokazu; Maehana, Junko; Horii, Taeko; Myohara, Yuki; Ogake, Naoko; Araki, Harumi; Fujimaki, Kazuo; Matsumura, Naoki; Kitayama, Rieko; et al. (CHEMOTHERAPY, 1994)
We studied the β-lactamase inhibitory activity of tazobactam (TAZ) and the in vitro and in vivo antibacterial activity of tazobactam/piperacillin (TAZ/PIPC). The following results were obtained. 1) TAZ inhibited various β-lactamases more effectively than sulbactam. A progressiv inhibition of TAZ against cephalosporinases was observed. 2) TAZ/PIPC exhibited a broad spectrum of antibacterial activity and potent activity against aerobic and anaerobic bacteria. 3) TAZ enhanced the activity of PIPC against PIPC-resistant bacteria such as Staphylococcus aureus (methicillin-susceptible), Staphylococcus epidermidis (methicillin-susceptible), Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Haemophilus influenzae, Moraxella catarrhalis and Bacteroides fragilis, and TAZ/PIPC was equally or more active than sulbactam/cefoperazone (SBT/CPZ), cefotiam and ceftazidime (CAZ) against P. aeruginosa, H. influenzae, M catarrhalis and B. fragilis resistant to PIPC. 4) The inducer activity of TAZ/PIPC for β-lactamase production was as low as that of PIPC. 5) TAZ/PIPC was more active than PIPC against rat pouch mixed infection caused by E. coli and penicillinase-producing S. epidermidis, rat intrauterine infection and mouse urinary tract infection caused by PIPC-resistant E. coli. TAZ/PIPC was more active than SBT/CPZ against rat pouch infection caused by P. aeruginosa highly resistant to CAZ.